DEVELOPMENT OF RESPONSIBILITY AND INITIATIVE SKILLS IN THE SOCIO-SPIRITUAL ACTIVITIES OF FUTURE ELEMENTARY SCHOOL TEACHERS - Ortiqova Dilsabo Munavvarjon kizi (Web of Journals Publishing, 2024)
This article provides information on the development of responsibility and initiative skills in the socio-spiritual activities of future elementary school teachers. Various methods and exercises are widely covered.
Keywords: Socio-spiritual activity, responsibility ability, brainstorming method, initiative ability, research method.